NILAI-NILAI PENDIDIKAN ISLAM DALAM BUDAYA MBOLO WEKI DI DESA MBAWA KECAMATAN DONGGO, BIMA - Haryanto, Adi; Tang, Muhammad; Palili, Sampara (Prodi PAI STIT Sunan Giri Bima, 2024)
Mbolo Weki culture, as an integral part of the daily life of the Mbawa Village community, has an important role in strengthening relations between religious communities. This research was carried out with the aim of providing a deeper understanding of the contribution of local culture in supporting the principles of Islamic education in the life of a multi-religious society. Qualitative research method with a phenomenological approach, exploring the meaning and experiences of the community in implementing Mbolo Weki culture. Data collection techniques through passive participant observation, semi-structured interviews, and documentation. Data analysis follows the stages of data reduction, data display, and conclusion drawing, which were developed by Miles, Huberman, and Saldana. Data validity through source triangulation, method triangulation, and time triangulation. The research results show that the Mbolo Weki culture in Mbawa Village contains Islamic educational values ​​which include: 1) the value of deliberation, in line with Islamic teachings regarding the importance of joint discussion in solving problems; 2) the value of cooperation/mutual cooperation, teaching the principle of mutual assistance in kindness; 3) the value of mutual respect and respect, which strengthens ukhuwah Islamiyah and tolerance between religious believers; 4) the value of caring, reflected in solidarity actions in social life; and 5) the value of politeness, prioritizing noble morals in social interactions.